Prediction of potential distribution areas and priority protected areas of Agastache rugosa based on Maxent model and Marxan model - Wang, Yongji; Zhao, Ruxia; Zhou, Xueyong; Zhang, Xiaolong; Zhao, Guanghua; Zhang, Fenguo (Frontiers in Plant Science, 2023)
Agastache rugosa (Fisch. & C. A. Mey.) Kuntze has been widely studied because of its high medicinal and edible value. Establishing the priority protected area of wild A. rugosa can provide scientific basis for the protection of germplasm resources. In this study, we predicted the potential suitability distribution area of A. rugosa under the current and future climate scenarios with the MaxEnt model, and the dominant climate factors affecting the distribution of A. rugosa were analyzed. Based on the above results, we predicted the priority protected areas of A. rugosa with the Marxan model. The results showed that A. rugosa is mainly distributed in the eastern and central regions of China at present. In future, the suitable area of A. rugosa will increase, otherwise a few areas will shrink back and migrate to the high latitude areas as a whole. Hydrothermal conditions are the main environmental factors affecting the distribution of A. rugosa. The priority protected areas of A. rugosa are mainly distributed in Chongqing, eastern Sichuan, southern Guizhou, western Hunan and Hubei and southwestern Shaanxi, which are basically consistent with the highly suitable areas predicted by Maxent model. The results of this study are of great significance for the protection and rational utilization of species of Agastache.